Pengujian Aktivitas Antioksidan Ekstrak Sonneratia ovata Backer. dari Desa Tongkaina, Bunaken sebagai Kandidat Zat Aktif Lotion - Mansauda, Karlah; Edy, Hosea Jaya; Sudewi, Sri (PHARMACON, 2025)
The mangrove leaves of Sonneratia ovata Backer, collected from Tongkaina Village, Bunaken, North Sulawesi, contain secondary metabolites such as flavonoids, saponins, tannins, alkaloids, steroids, and terpenoids. These secondary metabolites exhibit antioxidant activity and have potential to be developed as raw materials for natural medicines or cosmetics. This study aimed to evaluate the antioxidant activity and determine the IC₅₀ (Inhibitory Concentration 50%) value of the ethanol extract of S. ovata leaves using the DPPH (1,1-diphenyl-2-picrylhydrazyl) method. The ethanol extract of S. ovata leaves showed antioxidant activity at concentrations of 10, 20, 40, 60, and 80 ppm, with the highest inhibition percentage recorded at 71.47%. The IC₅₀ value obtained was 45.04 µg/mL against DPPH radicals, indicating that the S. ovata leaf extract collected from Tongkaina Village, Bunaken, North Sulawesi possesses very strong antioxidant activity. Keywords : extract, antioxidant, IC50, Sonneratia ovata Backer, lotion.